2005
DOI: 10.1177/000313480507100201
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Hepatic Resection for Metastatic Gastric Cancer

Abstract: The role of hepatic resection for metastatic gastric cancer is less well defined due to the tendency of gastric cancer to widely metastasize. The purpose of this study is to examine the beneficial effect of hepatic resection in patients with metastatic gastric cancer. The clinicopathologic features and long-term results of 11 patients who underwent hepatic resection for metastatic gastric cancer from January 1988 to December 1996 at Seoul National University Hospital were analyzed retrospectively. All resected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 7 publications
(10 reference statements)
0
28
0
1
Order By: Relevance
“…Zacherl et al 9 suggested that the in‐hospital mortality rate might be higher in patients who underwent synchronous hepatic resection than in those who underwent metachronous hepatic resection. In 12 reports 3–14 , three of four hepatic resection patients who died in hospital and had detailed documentation, underwent synchronous hepatic resection. Careful patient selection may be necessary, especially in the patients with synchronous hepatic metastases from gastric cancer.…”
Section: Mortality and Long‐term Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Zacherl et al 9 suggested that the in‐hospital mortality rate might be higher in patients who underwent synchronous hepatic resection than in those who underwent metachronous hepatic resection. In 12 reports 3–14 , three of four hepatic resection patients who died in hospital and had detailed documentation, underwent synchronous hepatic resection. Careful patient selection may be necessary, especially in the patients with synchronous hepatic metastases from gastric cancer.…”
Section: Mortality and Long‐term Resultsmentioning
confidence: 99%
“…The incidence of intrahepatic recurrence ranged from 47% to 73%. Although no papers in this series 3–14 have proven the efficacy of adjuvant chemotherapy, aggressive hepatic artery infusion chemotherapy might improve survival after hepatic resection 15–17 . Further investigation is necessary.…”
Section: Recurrencementioning
confidence: 92%
See 3 more Smart Citations